PENGEMBANGAN MEDIA BIG BOOK TERHADAP KEMAMPUAN LITERASI SISWA SEKOLAH DASAR - Hayati, Risaini Huli; Marhamah, Marhamah; Kuswidyanarko, Arief (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research aims to produce big book learning media for students' literacy skills in the material of recognizing the syllables "ga-, gi-, gu-, ge-, go-, gem-, gar-, and gim-" in class I Indonesian language learning SD Negeri 139 Palembang which is valid, practical and effective for use in the learning process. The quality of the products developed is assessed from the aspects of validity, practicality and effectiveness. This research method is an R&D research and development method using the ADDIE model, namely analysis, design, development, implementation and evaluation. The data collection techniques used were observation, interviews, questionnaires and documentation. The data analysis technique in this research is quantitative data analysis for validity, practicality and effectiveness. The results of this research show that this research produces a valid, practical and effective product. Valid based on the results of the validity assessment of 90.44%, practical based on the results of student and teacher assessments of 89.25%, and effective based on the results of the effectiveness assessment of 83 %. So it can be concluded that the big book media on students' literacy skills in learning Indonesian is valid, practical, and effectively used in the learning process.